Kajian Tingkat Risiko Tanah Longsor Desa Hargomulyo, Kecamatan Kokap, Kabupaten Kulonprogo - Nandra Eko Nugroho; Wisnu Aji Dwi Kristanto (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2019)
Landslides are one of the disasters that have a high frequency of events in DIY, especially in areas that are prone to landslides or potentially occur including the Hargomulyo Village, Kokap District, Kulonprogo Regency. Regulation of the Head of BNPB No. 2 of 2012 concerning the Disaster Risk Assessment Guide provides an understanding that disaster risk assessment is an approach to show potential negative impacts that may arise due to a potential disaster that strikes. From this function, disaster threat (H) and individual or community vulnerability (V) in a region are positively correlated or directly proportional to risk, meaning that when there are threats and certain areas are in vulnerability, the risk becomes very high. While capacity (C) correlates negatively or inversely, meaning that the higher the capacity of individuals or communities in a region, the risk will decrease. Disaster risk analysis and review have the subject, namely the existence of risky elements of certain disasters, are the livelihood assets and lives of a community or social system. The risk of landslides in the village of Hargomulyo is a process of combining the hazard index, vulnerability index and capacity index, based on the study of landslide hazards, vulnerability and capacity of the Hargomulyo Village. The results of overlays between hazard maps, vulnerability maps, and capacity maps indicate that the risk of landslide hazards in Hargomulyo Village is MODERATE.Keywords: Threat, Capacity, Vulnerability, Risk, Landslides.